2004
DOI: 10.1007/s00253-004-1843-8
|View full text |Cite
|
Sign up to set email alerts
|

Streptomycete spores entrapped in chitosan beads as a novel biocontrol tool against common scab of potato

Abstract: Spores of Streptomyces melanosporofaciens EF-76, an actinomycete that inhibits the growth of several plant pathogens, were incorporated in beads of chitosan and polyphosphate using the entrapment technique called complex coacervation. The degradation of spore-loaded beads was monitored by measuring the residual amount of chitosan in soil and by enumerating the S. melanosporofaciens population over time. After the introduction of spore-loaded chitosan beads into soil, the amount of chitosan in sterile soil rema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…The shift induced by chitosan in the soil microbial community occurred between 13 and 67 days after chitosan application. This delay could be attributed to both the kinetics of chitosan degradation (Jobin et al, 2005) and the fact that chitosan was not uniformly distributed in soil. Disturbance of microflora would possibly have been detected sooner at proximity to the seed tubers than in the bulk soil.…”
Section: Effects Of Chitosan and Ef-76 On Bacterial Communitiesmentioning
confidence: 98%
See 1 more Smart Citation
“…The shift induced by chitosan in the soil microbial community occurred between 13 and 67 days after chitosan application. This delay could be attributed to both the kinetics of chitosan degradation (Jobin et al, 2005) and the fact that chitosan was not uniformly distributed in soil. Disturbance of microflora would possibly have been detected sooner at proximity to the seed tubers than in the bulk soil.…”
Section: Effects Of Chitosan and Ef-76 On Bacterial Communitiesmentioning
confidence: 98%
“…Enumeration of GRA was carried out as previously described (Jobin et al, 2005). Briefly, bacterial pellets recovered from soil samples and from potato tubers were resuspended in 1 ml NaCl solution (0.85%).…”
Section: Enumeration Of Gra In Soil and On Potato Tubersmentioning
confidence: 99%
“…Indeed, chitin decomposing actinobacteria closely adhere to AMF spore walls (Selvakumar et al 2016) and the release of short chitin oligomers by chitinases leads to the activation of a signalling pathway involved in the first steps of AMF root colonization (Genre et al 2013). As an interesting way to introduce a chitinolytic actinobacterium in a plant production system, Jobin et al (2005) proposed the encapsulation of the microorganisms into chitosan beads. After their introduction in the environment, the beads could serve as carbon and nitrogen sources for the chitinolytic actinobacterium thus helping its implementation in the plant environment while the chitosan bead degradation would lead to the liberation of chitooligosaccharides that could act as elicitors of plant immunity responses (Jobin et al 2005).…”
Section: Chitinolytic Properties Of Actinobacteriamentioning
confidence: 99%
“…One could postulate that chitosan may contribute to disease suppression by eliciting plant defence mechanisms (Benhamou et al 1994) or by inhibiting the growth of the pathogen. This is unlikely the case since Jobin et al (2005) showed that chitosan beads were degraded within 1 wk after their addition to a soil substrate. The manure by-product used in this study was incubated in the presence of chitosan for over 1 wk before application on potato tubers.…”
Section: Discussionmentioning
confidence: 96%